'Assisting you to become a local': NGOs and constructed foreign spouses in Eastern Taiwan. Issue 1 (2nd January 2018) - Lin, Jun-Hua
Abstract: As social and cultural contexts change and globalization spreads, the number of transnational-marriage migrants mainly from Southeast Asia has increased in Taiwan. Using institutional ethnography, this article investigates the roles of local non-governmental organizations (NGOs) and projects aimed at helping foreign spouses to adapt to their new life. I mainly elaborate that NGOs emerge as important actors in assisting and empowering transnational spouses to 'become locals'. In empowerment projects, foreign spouses are given a voice to elaborate themselves. However, this article elaborates that these projects are a scheme of education to shape each such migrant into a proper 'Taiwanese wife/mother/daughter-in-law'. Also, these projects particularly promote 'exoticism' of migrants and become key sources of how local people understand the images of 'foreign spouses'. As a result, though NGOs play positive roles in empowering foreign spouses, we need to be aware that NGOs' efforts may ironically become a mechanism to strengthen transnational spouses' gender roles and cultural stereotypes.